PEMANFAATAN GEOGEBRA DALAM PEMBELAJARAN MATEMATIKA - Tanzimah Tanzimah (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
The digital age now opens opportunities for educators to utilize technology in their learning activities. One computer program that can be utilized in mathematics learning is GeoGebra. GeoGebra is a dynamic program that with a variety of facilities can be used as a medium for learning mathematics to demonstrate or visualize mathematical concepts and as a tool to construct mathematical concepts. This article presents a description of the GeoGebra program along with examples of the application of GeoGebra as a medium for learning mathematics.